Performance test for COD determination in wastewater using a closed reflux method with a COD reactor - Dita Setiawati; Yuris Diksy; Ardina Purnama Tirta (Indonesian Journal of Applied Environmental Studies, 2025)
Chemical Oxygen Demand (COD) is one of the test parameters to determine the water quality index. In environmental monitoring, valid test results of wastewater parameters are very important as a basis for making environmental policies. In this study, the determination of COD in wastewater refers to SNI 6989.73:2019 Determination of COD by Closed Reflux Titrimetric Method. The performance test of the COD determination method in wastewater samples was conducted on the parameters of precision, accuracy, and uncertainty estimation calculation of the bottom-up method, which was then compared to the acceptance criteria set by the laboratory. The performance test results for COD determination using the closed reflux method by titrimetry yielded a precision value with a percentage RSD of 3.33%; the accuracy test using the spiking technique was within the recovery range of 87-94%, and a relative uncertainty value of 7.23% at a COD concentration of 43.16 mg/L. All performance parameters of the method met the established acceptance criteria. COD determination using the closed reflux method in wastewater can be used for routine analysis.